Word of the Rector of the Nicolaus Copernicus University - Tretyn, Andrzej (Translational Research in Veterinary Science, 2018)
Under the new law of the constitution for science, the veterinary science discipline is recognized in the field of agriculture sciences. Herein Nicolaus Copernicus University (NCU), the highlight of this year was the introduction of a new graduate study program in veterinary medicine which started from October 1st 2018. Along with this new graduate study, I am now glad to introduce and launch an open access peered-reviewed journal “Translational Research in Veterinary Science” (TRVS) under NCU publishers. In the beginning phase, TRVS journal will publish two issues a year. In launching the TRVS, the aim was to produce a journal of scientific discipline which could be read both in Poland and abroad, and which would promote scientific activities within the scope of veterinary science.